2008
DOI: 10.1055/s-0028-1086092
|View full text |Cite
|
Sign up to set email alerts
|

Biological Profile of the Hyper/Oversulfated Chondroitin Sulfate Contaminant Isolated from Recalled Heparin

Abstract: An unexpectedly high rate of adverse events and deaths were reported from in patients exposed to heparin. Investigations on the quality of heparin revealed an oversulfated chondroitin sulfate (OSCS) contaminant in the heparin. Several reports on the chemical structure and limited biologic actions of OSCS have recently become available. However, no data are available on its anticoagulant and antiprotease effects. Moreover, its interaction with heparin, resulting in the modulation of heparin's anticoagulant acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…The triple detector method gave higher number average molecular weight, Mn, and weight average molecular weight, Mw, than the broad standard method, and this may be due to the use of an unfractionated heparin sample as the calibrant in the broad standard method which may not provide an accurate calibration for OSCS. Interestingly, the molecular weight observed for the purified OSCS material is lower (Mw 15740 versus 21100 and 21750) than the two synthetic tetra-sulfated versions and is similar to a previous observation [ 21 ] for OSCS. This is likely due to differences in the starting CS sample and /or ‘manufacturing’ process, in the same way that unfractionated heparin from different manufacturers possess different molecular weights [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The triple detector method gave higher number average molecular weight, Mn, and weight average molecular weight, Mw, than the broad standard method, and this may be due to the use of an unfractionated heparin sample as the calibrant in the broad standard method which may not provide an accurate calibration for OSCS. Interestingly, the molecular weight observed for the purified OSCS material is lower (Mw 15740 versus 21100 and 21750) than the two synthetic tetra-sulfated versions and is similar to a previous observation [ 21 ] for OSCS. This is likely due to differences in the starting CS sample and /or ‘manufacturing’ process, in the same way that unfractionated heparin from different manufacturers possess different molecular weights [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…Activation of kallikrein is confirmed by the present study with purified OSCS from adulterated heparin and two chemically prepared tetra sulfate chondroitin sulfates. All three materials were found to give a concentration dependent response, which is similar to a previous report [ 21 ] on OSCS from contaminated heparin in a prekallikrein assay. We have clearly shown that increasing the level of sulfation causes an increase in the ability of CS to generate kallikrein.…”
Section: Discussionsupporting
confidence: 88%
“…Studies using animal models of hemorrhage and thrombosis have indicated increased activities of the contaminated heparin compared to that of pure heparin. 14 According to these findings, if contaminated heparin was used in the production of LMWH, it cannot be excluded that the pharmacologic effects of the resultant LMWH could also be altered.…”
Section: Discussionmentioning
confidence: 99%
“…One study has identified the potential bleeding complications of CHs. 6 Contaminated heparin seems to bind to heparin cofactor II preferentially and thereby leads to inhibition of thrombin and bleeding complications. An increase of bleeding was described in some cases of patients exposed to contaminated preparations.…”
Section: Bleeding Complicationsmentioning
confidence: 99%
“…However, the advanced knowledge of the structureÀactivity relationship of sulfated glycosaminoglycans (GAGs) can be misused to develop adulterated heparin products that can lead to the unexpected adverse events and deaths such as those reported in 2008. 6 A new technique to detect other possible OSGAGs, such as oversulfated dermatan sulfate (OSDS), oversulfated heparan sulfate (OSHS), and OSGAGs, was recently published by Guerrini et al 7 It focused our attention to the possible involvement of other OSGAGs in the heparin contamination, since previous nuclear magnetic resonance (NMR) studies would not be able to differentiate OSCS from other OSGAGs, particularly OSHS. Guerrini et al were visionary in pointing out the possibility of other OSGAGs involved in the contamination issue.…”
Section: Introductionmentioning
confidence: 99%